ANALISIS AERODINAMIKA PADA AIRFOIL ATR72SM-IL DENGAN SIMULASI COMPUTATIONAL FLUID DYNAMICS - Cristian Davin Casey Gesner S (2021)
At this time, the technology is highly developed, one of which in the field of aeronautics or we are familiar with the technology of aircraft. It is important to know and define the magnitude of the lift force (elevator) and drag force (drag) on an airfoil aircraft. In this study used CFD software (Computational Fluid Dynamics) to determine the phenomenon of aerodynamic forces on the airfoil ATR72sm-il. In the process simulation will be carried out with the variation of angle of attack on the airfoil of 0o, 3o, 6o, 9o, 12o, 15o, 18o, 20o, and 23o. Making a model of the airfoil is 2D and is done in CFD software. In this simulation will be obtained velocity contours and the contours of the pressure, the value of Cl and Cd, as well as the value of Fl and Fd in any variation of angle of attack on an airfoil. In this study, the obtained maximum value of Cl and Fl by 1.491 and 21.871 N at an angle of 20o, while for the value of Cd and Fd not yet see signs of a maximum at an angle of 20o even until the angle of 23o. Based on the value of the obtained results of energy consumption to handle the presence of drag per-kilometer on the efficiency of fuel consumption. From the simulation results and the calculation will be taken the value and plotted in the graph to determine the values obtained. This study is expected to be useful for developments in the world of aeronautics, particularly related to the airfoil wing aircraft.